ANTONYMY OF PHRASEOLOGICAL UNITS - Jabborova, Anora (Журнал иностранных языков и лингвистики, 2021)
This article is about antonymic relationship of phraseological units. It discusses semantic features, semantic meanings and opposite meanings of phraseological units. There are given examples in English and Russian.